Studi Eksperimental Kuat Lentur Baja Ringan Profil C Sebagai Komponen Rangka Atap - Yudi Pranoto (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2020)
Cold frame is one of the alternatives to address the problem of the durability of the wood, but cold frame has a number of drawbacks, namely the high gravity, not easy in the manufacture of large span and require extra supervision strictly in its implementation and to make it. The purpose of this study is to analyze how big the power supple of profile C75.75.0,75 mild steel from three different products. Expect in this research, profile C-steel light can be used as a replacement of the roof frame of timber and concrete without overriding the power of the light steel profile C. From the results obtained as a result of the strong bending light steel C profile of each product. Powerful bending light steel profile C75.75.0,75 product Chi-Chi with span 1 m produced deflection of 14.7833 mm, the maximum load amounted to 86.8000 Kg and elastic tension of 1.0914 Kg/mm2, whereas in the span of 1.5 m with the same products and specifications the resulting deflection of 52.9533 mm, the maximum load of 80.0000 Kg and elastic tension of 1.0508 Kg/mm2. Powerful bending light steel profile C75.75.0,75 1 m span Truss with products generated deflection of 20.7600 mm, the maximum load amounted to 151.3333 Kg and elastic tension of 1.9512 Kg/mm2, whereas in the span of 1.5 m with the same products and specifications the resulting deflection of 43.6767 mm, the maximum load amounted to 126.3333 Kg and elastic tension of 1.4567 Kg/mm2. Powerful bending light steel profile C75.75.0 .75 product Kaso with span 1 m produced deflection of 21.0133 mm, the maximum load amounted to 164.0000 Kg and elastic tension of 2.1129 Kg/mm2, whereas in the span of 1.5 m with the same products and specifications the resulting deflection of maximum load 43.3333 mm amounted to 110.3333 Kg and elastic tension of 1.4379 Kg/mm2.